2016
DOI: 10.1007/s40556-016-0104-0
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Fetal Aberrant Right Subclavian Artery and Comparison with Other Second Trimester Markers for Down Syndrome Screening

Abstract: The chief objectives of our study were to assess the incidence and significance of fetal aberrant right subclavian artery (ARSA) in a nonreferral cohort of south Indian antenatal woman, and to compare it with other second trimester markers of Down syndrome. This was a prospective study conducted at Edappal hospital, India. After satisfying inclusion and exclusion criteria, 2000 consecutive antenatal women, seeking prenatal care and planning delivery at the same center, were recruited in a consecutive fashion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Of 57 studies identified through the electronic search and manual searching of references, 27 were assessed in full text, and of these, 14 were excluded (Table S2). Therefore, 13 studies, encompassing a total of 333 cases of isolated ARSA, were included in the review, of which seven involved retrospective and six prospective data acquisition (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 57 studies identified through the electronic search and manual searching of references, 27 were assessed in full text, and of these, 14 were excluded (Table S2). Therefore, 13 studies, encompassing a total of 333 cases of isolated ARSA, were included in the review, of which seven involved retrospective and six prospective data acquisition (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…One study included patients referred for fetal karyotyping by chorionic villus sampling (CVS) 18 and another described fetuses with a diagnosis of congenital vascular ring (including ARSA) 19 . In most studies, chromosomal testing was performed by conventional karyotyping, three also used fluorescence in-situ hybridization (FISH) for 22q11.2 microdeletion [24][25][26] and one included non-invasive prenatal testing 27 .…”
Section: Systematic Reviewmentioning
confidence: 99%